STUDY ON THE DIGESTIBILITY AND GROWH POTENTIAL OF ARTIFICIAL FEEDS IN Catla catla, Cirrhinus mrigala, Labeo rohita - F. Abbas; N. A. Qureshi; N. Khan; M. Ashraf; K. J. Iqbal (Journal of Animal and Plant Sciences, 2019)
Fingerlings of Indian major carps (Catla catla, Cirrhinus mrigala and Labeo rohita) were reared in quadruplicate in 0.6x0.9x0.6 m glass aquaria in monoculture systems to evaluate the digestibility of artificial feeds for three months. Two artificial feeds experimental (40% protein) and reference (25% protein) were prepared in which chromic acid was added as digestibility marker. Feeds were given H@ 4% of fish wet body weight twice a day. All the three species reared on experimental and control showed an equal growth trend. But when different species were compared among themselves, Cirrhinus mrigala yielded significantly higher (P ≤ 0.05) weight than Labeo rohita and Catla catla. A similar growth trend was observed in the control group whereas, Catla catla grew the least. When digestibility of different nutrients was compared, Catla catla in the control group digested protein (76.3±0.4%) equal to that of the experimental group (81.8±4.6%). Dry matter digestibility however, was significantly higher (P ≤ 0.05) in the experimental group than control. Unlike Catla catla, Labeo rohita and Cirrhinus mrigala digested protein significantly better (P ≤ 0.05) in experimental group showing their preference for more protein in formulated feeds. Digestibility of lipids and gross energy values did not differ significantly among species. It means that Labeo rohita and Cirrhinus mrigala prefer high protein diets than Catla catla. In case of acquisition of energy they are all equally efficient however, Cirrhinus mrigala is more efficient in extracting, digesting and assimilating different nutrients from artificial diets than Labeo rohita and Catla catla.
Keywords: Indian major carps; Fingerlings; Dry matter; Protein